2001
DOI: 10.1046/j.1365-2257.2001.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

The pathological consequences of anaemia

Abstract: Many patients with chronic diseases such as chronic renal failure, chronic inflammatory bowel disease and rheumatoid arthritis are anaemic. Recently congestive heart failure (CHF) has also been found to be associated with anaemia. In all these diseases this anaemia or chronic disease is at least partially due to excessive production of cytokines and leukotrines that interfere both with the effect of erythropoietin (EPO) at the bone marrow and the release of stored iron in the reticuloendothelial system. Treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 69 publications
1
40
1
5
Order By: Relevance
“…Results Hypertension BRAUNSTEIN et al [6] 55% had HT and 11% severe HT in the Medicare study (n=122,630 patients) HO et al [7] 39% of males and 59% of females had HT in the LEVY et al [8] Framingham study GUSTAFSSON et al [9] 27% of the males and 22% of the females had HT in the Danish Diamond study (n=5,491 patients) HIMMELMAN [10] At least 50% of patients with HT developed HF Diabetes KANNEL et al [24] Risk for developing HF in young males and females with DM (2.20 and 5.37, respectively) SHINDLER et al [25] In the SOLVD study 15% in the prevention trial and 26% in the treatment trial had DM COHN et al [26] Similar results in the V-HeFT II trial (26%) had DM Consensus trial [27] 23% developed DM in the CONSENSUS trial RYDEN et al [28] 19% developed DM in the ATLAS study SHINDLER et al [25] In the SOLVD registry (n=6,076 patients) 23% had DM ZANNAD et al [29] In the French registry study EPICAL 26% had DM BRAUNSTEIN et al [6] In the Medicare study (n=122,630 patients) 31% had DM STRATTION et al [30] Interrelationship between HbA1c levels and incidence of HF IRIBARREN et al [31] Each 1% increase in HbA1c was associated with 8% increased risk of developing HF PAOLISSO et al [32] Whole body insulin resistance is prevalent in HF patients with either ischaemic or idiopathic dilated cardiomyopathy SWAM et al [33] Similar results as in PAOLISSO et al [32] COPD BRAUNSTEIN et al [6] In the Medicare study 26% of patients had COPD GUSTAFSSON et al [9] In the Danish Diamond study 22% had COPD NI et al [53] In this study only 10% had COPD MCCULLOUGH et al [54] In this emergency department study 21% of the patients had COPD Anaemia TANNER et al [59] The prevalence of anaemia was 15% EZEKOWITZ et al [60] The prevalence of anaemia was 17% SILVERBERG et al [61] The prevalence of anaemia was 50% and in patients with severe HF 80% KOMAJDA [62] In this review the prevalence of anaemia and its clinical characteristics are discussed Table reprinted with permission from [39]; the numbers between brackets refer to references in …”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Results Hypertension BRAUNSTEIN et al [6] 55% had HT and 11% severe HT in the Medicare study (n=122,630 patients) HO et al [7] 39% of males and 59% of females had HT in the LEVY et al [8] Framingham study GUSTAFSSON et al [9] 27% of the males and 22% of the females had HT in the Danish Diamond study (n=5,491 patients) HIMMELMAN [10] At least 50% of patients with HT developed HF Diabetes KANNEL et al [24] Risk for developing HF in young males and females with DM (2.20 and 5.37, respectively) SHINDLER et al [25] In the SOLVD study 15% in the prevention trial and 26% in the treatment trial had DM COHN et al [26] Similar results in the V-HeFT II trial (26%) had DM Consensus trial [27] 23% developed DM in the CONSENSUS trial RYDEN et al [28] 19% developed DM in the ATLAS study SHINDLER et al [25] In the SOLVD registry (n=6,076 patients) 23% had DM ZANNAD et al [29] In the French registry study EPICAL 26% had DM BRAUNSTEIN et al [6] In the Medicare study (n=122,630 patients) 31% had DM STRATTION et al [30] Interrelationship between HbA1c levels and incidence of HF IRIBARREN et al [31] Each 1% increase in HbA1c was associated with 8% increased risk of developing HF PAOLISSO et al [32] Whole body insulin resistance is prevalent in HF patients with either ischaemic or idiopathic dilated cardiomyopathy SWAM et al [33] Similar results as in PAOLISSO et al [32] COPD BRAUNSTEIN et al [6] In the Medicare study 26% of patients had COPD GUSTAFSSON et al [9] In the Danish Diamond study 22% had COPD NI et al [53] In this study only 10% had COPD MCCULLOUGH et al [54] In this emergency department study 21% of the patients had COPD Anaemia TANNER et al [59] The prevalence of anaemia was 15% EZEKOWITZ et al [60] The prevalence of anaemia was 17% SILVERBERG et al [61] The prevalence of anaemia was 50% and in patients with severe HF 80% KOMAJDA [62] In this review the prevalence of anaemia and its clinical characteristics are discussed Table reprinted with permission from [39]; the numbers between brackets refer to references in …”
Section: Studymentioning
confidence: 99%
“…Anaemia in chronic illness is characterised by weakness, fatigue, cachexia and poor nutritional state, and by impaired mood, cognitive functions and quality of life [62]. It has been suggested that anaemia to some extent contributes to exercise limitation and dyspnoea in chronic illness [63].…”
Section: Anaemiamentioning
confidence: 99%
“…Данное состоя-ние (см. таблицу) характеризуется двух-или трехростковой цитопенией и развивается при воздействии миелодепрес-сивных факторов, в частности как побочное действие при приеме цитостатиков [18,20]. При аутоиммунной гемоли-тической анемии (ГА) диагностическим критерием являет-ся положительная прямая проба Кумбса с тепловыми анти-телами, иногда выявляется повышение количества ретику-лоцитов ≥12‰.…”
Section: особенности анемии у больных ревматоидным артритомunclassified
“…Также было доказано, что анемия приводила к выражен-ному снижению работоспособности (как у мужчин, так и у женщин) и уровень Hb коррелировал с показателями КЖ больных РА [18]. Длительно существу-ющая хроническая анемия приводит к гипоксии тканей, нарушает психический статус, вызывает нарушения в сер-дечно-сосудистой системе с формированием «анемическо-го сердца», а в запущенных случаях приводит к более выра-женным изменениям, в частности, к сердечной недостаточ-ности, существенно ухудшающей прогноз у этих больных [19][20][21]. В исследовании ANCHOR [22] среди пациентов (n=59 772) с сердечно-сосудистой недостаточностью (воз-раст 71,8±11,4 года) анемия была диагностирована в 42% случаев.…”
unclassified
“…Apart from being free from RBC transfusions, the benefits have included improvements in life quality, cognitive function, stamina, and the prevention of left ventricular hypertrophy. 5 These triumphs stimulated further clinical trials and off-label uses of ESAs that have, over time, proven how complex and potentially detrimental use of biologic agents may be. First, investigators and primary care physicians extrapolated the data to ask why or in many cases simply assume that raising hemoglobin levels (Hb) into the normal range would further improve clinical outcomes.…”
mentioning
confidence: 99%